High temperature noble gas thermometry in Lake Kivu - Schwenk, Cornelis; Negele, Sophie; Balagizi, Charles M.; Aeschbach, Werner; Boehrer, Bertram (SSRN, 2022)
Due to their biological and chemical inertness, noble gases in natural waters are widely used to trace natural waters and to determine ambient temperature conditions during the last intensive contact with the atmosphere (equilibration). Thus far, only common environmental conditions have been considered, and hence investigated temperatures have almost never exceeded 35 °C, but environmental scenarios that generate higher surface-water temperatures (such as volcanism) exist nonetheless. We make use of newly determined solubility data at higher temperatures to analyze data of unexpectedly low noble gas concentrations in the deep water of Lake Kivu by applying various approaches of noble gas thermometry. Noble gas concentration ratios and least squares fitting of individual concentrations indicate that the data agrees best with the assumption that deep water originates from groundwater formed at temperatures of about 65 °C. Thus, no form of degassing is required to explain the observed noble gas depletion: the deep water currently contained in Lake Kivu has most probably never experienced a large scale degassing event. This conclusion is important as limnic eruptions were feared to threaten the lives of the local population